Human waste used as nesting material affects nest cooling in the clay-colored thrush - Corrales Moya, Josué (2021)
The internal temperature of nests largely depends on the materials used in their construction because the characteristics of each material affect the isolation of nest walls. In urban environments, the availability of natural materials for nest building decreases, while the availability of artificial materials increases. Therefore, many urban bird species use more artificial materials for nest building inside cities, which may affect the thermal properties of the nest. We conducted an experiment to measure the effect of artificial materials included as part of the nest structure, on nest thermoregulation. We used as a model, nests of the clay-colored thrush (Turdus grayi), an urban bird species that have been reported using artificial nest materials. In our experiment, we measured how variation in artificial materials mass affects the nest cooling rate in a climate-controlled room. We found that artificial materials increased the cooling rate of clay-colored thrush nests, compared with nests with only natural materials. This result is especially relevant because showed a negative direct effect of the use of artificial material for nest building in birds. Considering that the availability of artificial material is increasing in urban areas, while natural material is decreasing, it is expected that the negative effect of using artificital material for nest construction would increase in the clay-colored thrush and other city bird species.